Direct quantitation of therapeutic antibodies for pharmacokinetic studies using immuno-purification and intact mass analysis. (8th February 2019) - Vasicek, Lisa A; Zhu, Xin; Spellman, Daniel S; Bateman, Kevin P
Aim: The quantitation of therapeutic antibodies by MS often utilizes a surrogate peptide approach. Recent enhancements in instrumentation and sample preparation have enabled quantitation by detection of the intact molecule using MS.Methods & Results: A comparison of three methods for quantitative analysis of therapeutic monoclonal antibodies including analysis after deglycosylation, after hinge digestion and at the fully intact antibody level is reported. The optimized methodology provided sensitivity down to 0.1 μg/ml and a lower limit of quantitation of 0.5 ug/ml from a 30 μl sample volume.Conclusion: Application of this approach to a pharmacokinetic study compared with a conventional surrogate peptide and a ligand-binding assays provided consistent data with direct detection of the dosed molecule.